Crigler-Najjar Syndrome: A Rare Fatality - Alizah Alaman; Munira Minaz Ali; Nazish Hussain Ali Pachani; Anmol Minaz Ali (International Journal on Women Empowerment, 2016)
This paper reviews Crigler-Najjar Syndrome as a rare fatality affecting individuals in the early years of life. It’s rare incidence, mis-diagnosis and severe complications resulting in death at the early age has cause difficulty in determining its exact frequency in general population. This syndrome, is described by the accumulation of un-conjugated bilirubin in the body due to the inheritance of defects UGT1A1 genes. This anomaly disrupts the bilirubin mechanism at a greater extent. The high level of bilirubin in the body manifests itself in terms of specific signs and symptoms among which jaundice is most common and well-known. Therefore, treatment is primarily directed towards decreasing accumulation of un-conjugated bilirubin in the body. Aspects of liver transplant can be seen as permanent treatment plan at risk to benefit ratio.